In-situ investigation of bubble dynamics and two-phase flow in proton exchange membrane electrolyzer cells. (14th June 2018) - Li, Yifan; Kang, Zhenye; Mo, Jingke; Yang, Gaoqiang; Yu, Shule; Talley, Derrick A.; Han, Bo; Zhang, Feng-Yuan
Abstract: Gas bubble dynamics and two-phase flow have a significant impact on the performance and efficiency of proton exchange membrane electrolyzer cells (PEMECs). It has been strongly desired to develop an effective experimental method for in-situ observing the high-speed/micro-scale oxygen bubble dynamics and two-phase flow in an operating PEMEC. In this study, the micro oxygen bubble dynamic behavior and two-phase flow are in-situ visualized through a high-speed camera coupled with a specific designed transparent PEMEC, which uses a novel thin liquid/gas diffusion layer (LGDL) with straight-through pores. The effects of different operating conditions on oxygen bubble dynamics, including nucleation, growth, and detachment, and two-phase flow have been comprehensively investigated. The results show that temperature and current density have great effects on bubble growth rate and reaction sites while the influence of flow rate is very limited. The number, growth rate, nucleation site, and slug flow regime of oxygen gas bubbles increase as temperature and/or current density increases, which indicates that an increase in temperature and/or current density can enhance the oxygen production efficiency. Further, a mathematical model for the bubble growth is developed to evaluate the effects of temperature and current density on the bubble dynamics. A mathematical model has been established and shows a good correlation with the experimental results. The studies on two-phase flow and high-speed micro bubble dynamics in the microchannel will help to discover the true electrochemical reaction at micro-scale in an operating PEMEC. Highlights: Rapid micro oxygen bubble generation and growth are in-situ visualized. Bubble growth rate and reaction sites are increased with the current density. A model shows a good agreement with the experiment results. Annular flow is more easily to form under high current densities.